Diet Adherence among Type 2 Diabetes Mellitus Patients at Pekauman Public Health Center - Muhammad Rais Faisal; Rusdiana Silaban (Jenggala : Jurnal Riset Pengembangan dan Pelayanan Kesehatan, 2025)
Type 2 Diabetes Mellitus (T2DM) is a chronic metabolic disorder characterized by persistent hyperglycemia, which requires long-term management including strict dietary adherence. Non-adherence to dietary recommendations increases the risk of poor glycemic control and diabetes-related complications. This study aimed to describe the level of diet adherence among patients with T2DM at Pekauman Public Health Center in 2023. A descriptive cross-sectional study was conducted in July 2023 involving 30 respondents with T2DM who met the inclusion criteria. Data were collected using a structured questionnaire assessing adherence to dietary components including portion size, food type, and meal schedule. Data were analyzed using univariate methods to generate frequency distributions. Of the 30 respondents, 53.3% were non-adherent to dietary portion control, 66.7% were non-adherent to food type recommendations, and 56.7% were non-adherent to meal schedule adherence. Most respondents were female (73.3%), aged >50 years (50%), with the majority having senior high school education (36.7%) and working as housewives (46.7%). The majority of T2DM patients at Pekauman Public Health Center did not adhere to recommended dietary guidelines in terms of portion size, food type, and meal schedule. Strengthened health education and multidisciplinary collaboration between doctors, nutritionists, and community health workers are essential to improve dietary adherence and prevent complications.